Pembelajaran Al-Qur'an dengan Model Flipped Classroom pada Mata Pelajaran PAI untuk Mengefektifkan Waktu dan Sumber Daya Manusia pada Sekolah Menengah Pertama - Purnasari, Martina (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
This research aims to explore the implementation of the Flipped Learning method in seventh-grade students at Middle School of Wiraguna Limbangan, Garut by conveying its strengths and weaknesses, with a focus on situations or events related to research problems in learning innovation. The scope is limited to efforts to uncover problems and challenges within the learning context. The research adopts a qualitative descriptive field research approach. The research subjects consist of 30 students from Wiraguna Limbangan Middle School in the subject of Islamic Religious Education (PAI). Data were collected through semi-structured interviews, classroom observations, and workgroup observations. The research findings conclude that students have engaged in learning activities using the flipped learning method according to their respective roles. Reading materials and participation in discussions indicate that students are active and responsible in the learning process that employs the flipped learning method. Effective learning through flipped classes is supported by the use of technology and engaging media.